Pengaruh Perilaku Konsumen terhadap Loyalitas Pembelian di Masa New Normal (Studi Kasus pada OneZo Indonesia) - Stephanie Rosanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The COVID-19 pandemic has changed the lives of all of us in many ways, including the type of food and consumption patterns. These changes are likely to have great impacts and take effect for a long period of time. An industry that is closely related to major changes, namely the world of Food and Beverage (F&B). COVID-19 and the restriction scheme issued by the government will determine changes in the way to obtain F&B needs. One of the factors that must be considered is consumer behavior in order to gain customer loyalty. There are four factors that influence consumer behavior, namely cultural, social, personal and psychological factors. The research method used is by distributing questionnaires to consumers from OneZo Indonesia. The results of data processing from the validity and reliability test show that all questions are valid because the r-count value > 0.36 (r-table value) and the Crobach's Alpha value is 0.875 or greater than 0.80 so it can be concluded that the research instrument used used is reliable and is in the interval 0.80 – 1.00 or is in the category of a very high level of reliability. Based on the results of the Coefficient of Determination Test, the four independent variables have an influence on the dependent variable, namely Purchase Loyalty of 0.79 or 79%. The order of factors from the most influential to the least influential are Personal, Social, Cultural, and Psychology. The amount of variation of the dependent variable that can be explained by the independent variable is 79%, while the other 21% can be explained by other variables not examined in this study.